(untitled) (Research, Society and Development, 2020)
This study aimed to map and characterize possible international scientific publications in the Web of Science database that punctually address content marketing on digital platforms. A bibliometric analysis of 92 publications found in the aforementioned database was carried out, together with a textual analysis of the three articles with the highest number of citations. After analyzing the results, it was found that 2018 was the year with the highest number of publications, the United States is the country that published the most on the subject and the three most cited articles are found in Qualis Periodicals A1, A1 and B2.